Quality of university teaching and student satisfaction at the Faculty of Economic Engineering, Statistics and Social Sciences of UNI. - Quiroz Vera, Eduardo Fernando (2016)
When assessing organizational quality in a university, an important aspect is to evaluate user satisfaction. Since students are the main users of universities, the ability to evaluate the quality of the educational services they provide is very important. The general objective of this research was to determine if there is a relationship between the level of satisfaction of the students of the Faculty of Economic Engineering, Statistics and Social Sciences of the National University of Engineering and the level of importance they give to the services and products they receive. For this purpose, use was made of the SATEST scale, developed by Bullón (2007) and modified by Watson (2013), which made it possible to know the characteristics of satisfaction in these students. The eight areas resulting from the scale reflect the diversity of factors that influence student satisfaction, and affirm that satisfaction with the educational service is influenced by formal educational aspects such as the curriculum, academic demands, the teaching-learning process; as well as by aspects linked to the educational context, such as infrastructure, the offer of extracurricular activities, the relationship of the FIEECS with the social context, and finally, by the services provided by the university, such as, for example, the medical service. As a result, it is concluded that students show high satisfaction, since they are satisfied with the quality of education provided by the School. The Statistical Engineering students are more satisfied than the Economic Engineering students in all areas of satisfaction. The most notable areas are Interpersonal relations with other members of the faculty, Connection of the faculty with the context, Medical service, and Curriculum and academic demands. From the results of the survey, it was found that the groups of students -according to sex, age, study cycle, university entrance cycle- did not differ statistically in the areas of satisfaction. The results indicate that students give greater weight to the areas Curriculum and academic demands and Teaching/learning process. This shows that students give a high value to these two key aspects within the student's training process.